Magnetization Transfer Ratio in Lower Limbs of Late Onset Pompe Patients Correlates With Intramuscular Fat Fraction and Muscle Function Tests - Nuñez-Peralta, Claudia; Montesinos, Paula; Alonso-Jiménez, Alicia; Alonso-Pérez, Jorge; Reyes-Leiva, David; Sánchez-González, Javier; Llauger-Roselló, Jaume; Segovia, Sonia; Belmonte, Izaskun; Pedrosa, Irene; Martínez-Noguera, Antonio; Matellini-Mosca, Briano; et al. (Frontiers in Neurology, 2021)
Objectives: Magnetization transfer (MT) imaging exploits the interaction between bulk water protons and protons contained in macromolecules to induce signal changes through a special radiofrequency pulse. MT detects muscle damage in patients with neuromuscular conditions, such as limb-girdle muscular dystrophies or Charcot-Marie-Tooth disease, which are characterized by progressive fiber loss and replacement by fatty tissue. In Pompe disease, in which there is, in addition, an accumulation of glycogen inside the muscle fibers, MT has not been tested yet. Our aim is to estimate MT ratio (MTR) in the skeletal muscle of these patients and correlate it with intramuscular fat fraction (FF) and results of muscle function tests. Methods: We obtained two-point axial Dixon and Dixon-MT sequences of the right thigh on a 1.5 Teslas MRI scanner in 60 individuals, including 29 late onset Pompe disease patients, 2 patients with McArdle disease, and 29 age and sex matched healthy controls. FF and MTR were estimated. Muscle function using several muscle function tests, including quantification of muscle strength, timed test quality of life scales, conventional spirometry obtaining forced vital capacity while sitting and in the supine position, were assessed in all patients. Results: MTR was significantly lower in Pompe patients compared with controls (45.5 ± 8.5 vs. 51.7 ± 2.3, Student T-test, p < 0.05). There was a negative correlation between the MTR and FF muscles studied (correlation coefficient: −0.65, Spearman test: p < 0.05). MTR correlated with most of the muscle function test results. We analyzed if there was any difference in MTR values between Pompe patients and healthy controls in those muscles that did not have an increase in fat, a measure that could be related to the presence of glycogen in skeletal muscles, but we did not identify significant differences except in the adductor magnus muscle (48.4 ± 3.6 in Pompe vs. 51 ± 1.3 in healthy controls, Student T-test = 0.023). Conclusions: MTR is a sensitive tool to identify muscle loss in patients with Pompe disease and shows a good correlation with muscle function tests. Therefore, the MT technique can be useful in monitoring muscle degeneration in Pompe disease in clinical trials or natural history studies.